Organisational culture as a significant factor of competitive advantage in primary health care units - Sikora, Tomasz; Kanecki, Krzysztof; Sikora, Agnieszka; Nitsch-Osuch, Aneta; Bogdan, Magdalena (Family Medicine & Primary Care Review, 2022)
The competitiveness of contemporary organisations is the foundation of their growth and market operation. Organisational culture, integrating the activities of an organisation with the environment in its own manner, determines the way it adapts to the conditions, and considerably impacts the competitive standing of a business. This is particularly important but, at the same time, increasingly difficult for entities operating on the health care market where goods of the highest order, namely saving life and improving health, are provided. The purpose of this article is to present a theoretical and practical discussion of the essence of the impact of organisational culture on building the competitive advantage of health care providers. The article features both a theoretical discussion based on a literature review and a practical discussion analysing the impact of organisational culture on the competitiveness of the health care provider Corten Medic. Both dimensions of the discussion reveal that organisational culture plays an essential role in building the competitive edge of a company and achieving success. In literature on the subject regarding enterprises operating in the health care sector, little attention is given to the links between organisational culture and the competitiveness of health care providers, although, as demonstrated by the results of this article, they may be highly significant, both for management as well as for patients. The article presents an attempt to define the essence and impact of organisational culture on establishing a competitive advantage.